Exploring the Impact of Hyperbolic Figures of Speech Analysis in 'The Greatest Showman' Theme - Nyoman Widhi Wisesa; Komariyah Komariyah; Latifah Latifah (International Forum of Researchers and Lecturers, 2024)
This study explores the impact of hyperbolic figurative analysis in the theme of the film